The renaissance of marriage in fifteenth-century Italy - D'Elia, Anthony F. 1967- (Harvard historical studies, 2004)
Introduction -- Marriage and wisdom form antiquity to the renaissance -- The revieal of the ancient Epithalanium in courtly weddings -- Weddings as propaganda : rhetoric and court culture -- The culture of marriage and sex in Italian courts -- Humanist criticisms of celibacy adn the reformation